Importance of standardized DXA protocol for assessing physique changes in athletes - Nana, A.; Slater, G. J.; Hopkins, W. G.; Halson, S. L.; Martin, D. T.; West, N. P.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The implications of undertaking DXA scans using best practice protocols (subjects fasted and rested) or a less precise but more practical protocol in assessing chronic changes in body composition following training and a specialized recovery technique were investigated. Methods: Twenty-one male cyclists completed an overload training program, in which they were randomized to four sessions per week of either cold water immersion therapy or control groups. Whole-body DXA scans were undertaken with best practice protocol (Best) or random activity protocol (Random) at baseline, after 3 weeks of overload training, and after a 2-week taper. Magnitudes of changes in total, lean and fat mass from baseline-overload, overload-taper and baselinetaper were assessed by standardization ( mean/SD). Results: The standard deviations of change scores for total and fat-free soft tissue mass (FFST) from Random scans (2-3%) were approximately double those observed in the Best (1-2%), owing to extra random errors associated with Random scans at baseline. There was little difference in change scores for fat mass. The effect of cold water immersion therapy on baseline-taper changes in FFST was possibly harmful (-0.7%; 90% confidence limits ±1.2%) with Best scans but unclear with Random scans (0.9%; ±2.0%). Both protocols gave similar possibly harmful effects of cold water immersion therapy on changes in fat mass (6.9%; ±13.5% and 5.5%; ±14.3%, respectively). Conclusions: An interesting effect of cold water immersion therapy on training-induced changes in body composition might have been missed with a less precise scanning protocol. DXA scans should be undertaken with Best.